Reorganization of elderly care in a primary health care service through the Altadir method of popular planning - Hellen Pollyanna Mantelo Cecilio (Investigación y Educación en Enfermería, 2013)
This paper’s objective was to describe the experience of students and professors in selecting problems and developing strategies to solve these problems using the Altadir method of popular planning during the undergraduate nursing program at the State University of Maringá, Paraná (Brazil). The problem selected was care provided to elderly patients in a primary health care service. This paper provides a reflection on the use of the Altadir method to improve the quality of care delivered to this population.